2022
DOI: 10.4102/sajce.v12i1.1119
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for access to early childhood development services for children with disabilities in South Africa

Abstract: Priorities for access to early childhood development services for children with disabilities in South Africa',

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…A comprehensive process of screening, identification, assessment and support is outlined, including the use of standardised tools and collaboration with parents and other professionals. However, apparently, many ECD centres are either not aware of the need to conduct assessments for disability or lack the necessary resources to do so (Karisa et al 2022 ). This finding is based on the results of an audit of ECD centres in 2014, which showed that assessments of children with disabilities are generally very low across all disability types (Department of Education’s National audit of ECD services [Department of Social Development 2014 ]).…”
Section: Contextual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive process of screening, identification, assessment and support is outlined, including the use of standardised tools and collaboration with parents and other professionals. However, apparently, many ECD centres are either not aware of the need to conduct assessments for disability or lack the necessary resources to do so (Karisa et al 2022 ). This finding is based on the results of an audit of ECD centres in 2014, which showed that assessments of children with disabilities are generally very low across all disability types (Department of Education’s National audit of ECD services [Department of Social Development 2014 ]).…”
Section: Contextual Backgroundmentioning
confidence: 99%
“…However, in both countries, the major obstacles preventing children from accessing quality education at ECE level include negative attitudes towards disability, and a lack of resources, funding, facilities and trained personnel to effectively cater to the diverse needs of children with disabilities (Dombrowski, Sitabkhan & Kilonzo 2023 ). Unfortunately, major gaps remain and the checking and evaluating of ECE programmes has been inconsistent and opaque at times, with scant regard for improving access to quality-inclusive ECE and no acknowledgement that the barriers to access are not insurmountable (Karisa et al 2022 ; Samuels et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%